في البرنامج العلاجي لتعليم اللغة العربية المكثف بالجامعة كياهي الحاج عبد الرحمن واحد بكالونجان الإسلامية الحكومية(SRL) تعليم علم النحو على ضوء التعلم المنظم الذاتي: Pengajaran Tata Bahasa Arab Berbasis Pembelajaran Berbasis Pengaturan Diri (SRL) dalam Program Intensif Perbaikan Bahasa Arab - Muhammad Zayinil Akhas; M. Fairuz Rosyid; Ahmad Ubaedi Fathuddin (Language Development Center, 2025)
Background: Grammar teaching in Arabic language learning often fails to encourage student independence and motivation, especially in the context of remedial programs. Purpose: This study aims to examine the application of Self-Regulated Learning (SRL) strategies in grammar teaching in an intensive Arabic remedial program at UIN K.H. Abdurrahman Wahid Pekalongan. Method: This study employs a qualitative descriptive approach with a non-experimental field design, involving 23 students selected purposefully due to their low grammar proficiency. Data were collected through observation, SRL questionnaires, pre- and post-tests, and in-depth interviews. Data analysis was conducted qualitatively and quantitatively to evaluate the effectiveness of the SRL strategy and its impact on grammar mastery. Results and Discussion: The results of the study showed a significant improvement in students' grammar comprehension after the implementation of the SRL strategy. Students demonstrated increased independence, motivation, and engagement in grammar learning. SRL components such as planning, self-monitoring, and reflection were proven effective in addressing grammar learning challenges in an intensive short-term environment. Conclusions and Implications: These findings indicate that integrating SRL into Arabic grammar instruction can improve learning outcomes and foster student independence. This study contributes to the development of SRL theory in language learning and offers practical implications for designing more effective remedial programs in Arabic language education. The integration of Self-Regulated Learning in Arabic grammar instruction in remedial programs not only improves mastery of the material but also fosters the independent learning character essential for long-term academic development. Therefore, this approach is recommended for widespread adoption in Arabic language learning programs in higher education, with the support of policies, faculty training, and adequate learning resources.